2007
DOI: 10.1016/j.molimm.2006.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Expression of β-defensins pBD-1 and pBD-2 along the small intestinal tract of the pig: Lack of upregulation in vivo upon Salmonella typhimurium infection

Abstract: Defensins are antimicrobial peptides that play an important role in the innate immune response in the intestine. Up to date, only one ␤-defensin (pBD-1), has been described in pig, which was found to be expressed at low levels in the intestine. We set-up a quantitative PCR method to detect the gene expression of pBD-1 and a newly discovered porcine ␤-defensin, pBD-2. Expression of pBD-1 mRNA increased from the proximal to the distal part of the intestine whereas pBD-2 expression decreased. The main gene expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
29
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 38 publications
(28 reference statements)
7
29
0
Order By: Relevance
“…In the present study, mRNA of three β-defensins was diversely expressed in the tissues that require strong mucosal defenses, particularly the tongue, which was consistent with the expression pattern described previously in pigs (Zhang et al 1998;Veldhuizen et al 2007), sheep (Huttner et al 1998), and cattle (Stolzenberg et al 1997). Previously we found that the cathelicidin molecules, the other important antimicrobial peptides family, were generally expressed at low levels in the tongue in both breeds (Ma et al 2014).…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, mRNA of three β-defensins was diversely expressed in the tissues that require strong mucosal defenses, particularly the tongue, which was consistent with the expression pattern described previously in pigs (Zhang et al 1998;Veldhuizen et al 2007), sheep (Huttner et al 1998), and cattle (Stolzenberg et al 1997). Previously we found that the cathelicidin molecules, the other important antimicrobial peptides family, were generally expressed at low levels in the tongue in both breeds (Ma et al 2014).…”
Section: Discussionsupporting
confidence: 92%
“…Following treatment with most toxins, mRNA expression was significantly affected for both genes, though cell supernatant levels of pBD-1 and pBD-2 were not significantly changed. In this study, the expression of pBD-1 and pBD-2 was shown to be low and is similar to what has been reported for other cells (10,24,31). It has previously been suggested that this basal level of expression may reflect a potential for upregulation of these defensins upon bacterial infection, and upregulation of these defensins has been reported following Salmonella infection (10,24).…”
Section: Discussionsupporting
confidence: 89%
“…Previous experiments have shown that exposure to several mycotoxins may increase susceptibility to experimental or natural mucosal infections by inducing bacterial translocation and colonization across the intestinal epithelium (21,22), but no data are available examining the role mycotoxin combinations may play in intestinal infections. Reports have been done demonstrating that the antimicrobial activity of AMPs, such as ␤-defensins, may be associated with bacterial populations in the intestine, which naturally present a barrier limiting undesirable gut mucosal infections (23)(24)(25). Accordingly, we hypothesized that a mixture of naturally cooccurring Fusarium toxins that can be observed in food exert significant effects on the synthesis and secre-tion of AMPs compared to their effects as individual toxins.…”
mentioning
confidence: 99%
“…mBD3, similar to certain human b-defensins, possesses the ability to attract immune cells chemotactically (54). To date, 12 pBDs have been identified, and the expression of pBD1 and pBD2 in the small intestine of the pig has been described recently (55,56).…”
Section: Discussionmentioning
confidence: 99%